Cyclic oxidation behavior of a multilayer composite coating for single-crystal superalloys. (December 2018) - Ren, Pan; Yang, Yingfei; Li, Wei; Zhu, Shenglong; Wang, Fuhui
Highlights: A multilayer composite coating was prepared, which comprised of alternating Ni + CrAlYSiHfN sub-layers and Alx N sub-layers. In cyclic oxidation, the oxide scale formed on multilayer coating exhibits good spallation resistance due to its lower CTE mismatch. Tax O formed within the TGO of N5 substrate, and breaks the continuity and integrity of α-Al2 O3 scale because of large PBR of Tax O. The θ-to-α transformation of Al2 O3 on multilayer coating leads to a slight decrease in resiudal stress in the initial oxidation stage. Abstract: A multilayer composite coating, comprised of alternating Ni + CrAlYSiHfN sub-layers and Alx N sub-layers, was manufactured by magnetron sputtering. The multilayer is composed of β-NiAl, α-Cr and AlN phases after annealing, and their volume fractions are 72 vol.%, 12 vol.% and 16 vol.%, respectively. Due to doping with nitrides, the CTE of multilayer coating is reduced to around 12.7*10 −6 /K. The lower CTE mismatch allows multilayer coating to exhibit good resistance to oxide scale spalling in thermal cycling at 1100 °C. The θ-to-α Al2 O3 transformation in oxide scale caused a small drop of residual stresses on multilayer coating in initial oxidation stage.